The short-chain fatty acid receptors Gpr41/43 regulate bone mass by promoting adipogenic differentiation of mesenchymal stem cells - Behler-Janbeck, Friederike; Baranowsky, Anke; Yorgan, Timur A.; Jaeckstein, Michelle Y.; Worthmann, Anna; Fuh, Marceline M.; Gunasekaran, Karthikeyan; Tiegs, Gisa; Amling, Michael; Schinke, Thorsten; Heeren, Joerg (Frontiers in Endocrinology, 2024)
Bone is a dynamic tissue that is constantly remodeled throughout adult life. Recently, it has been shown that bone turnover decreases shortly after food consumption. This process has been linked to the fermentation of non-digestible food ingredients such as inulin by gut microbes, which results in the production of the short-chain fatty acids (SCFAs) acetate, propionate and butyrate. SCFAs exert various metabolic functions, which in part can be explained by activation of G protein-coupled receptors (Gpr) 41 and 43. However, the potential relevance of a SCFA-Gpr41/43 signaling axis for bone metabolism has not been established. The aim of our study is to investigate the role of Gpr41/43 in bone metabolism and osteogenic differentiation of mesenchymal stem cells. For this purpose, we analyzed the skeletal phenotype of wild type controls (WT) and Gpr41/43 double knockout (Gpr41/43 dKO) mice fed either a chow or an inulin-enriched diet. In addition, we isolated bone marrow derived mesenchymal stem cells from WT and Gpr41/43 dKO mice and differentiated them into osteoblasts in the absence or presence of acetate. MicroCT scanning of femoral bones of Gpr41/43 dKO mice revealed a significant increase of trabecular bone volume and trabecular compared to WT controls. Treatment of WT bone marrow-derived osteoblasts with acetate resulted in decreased mineralization and substantial downregulation of bone formation markers such as Phex, Ptgs2 and Col1a1. Notably, this effect was strongly attenuated in differentiated osteoblasts lacking Gpr41/43. Inversely, acetate supplementation resulted in higher levels of adipocyte marker genes including Pparg, Lpl and Adipoq in bone marrow-derived cells from WT mice, an effect blunted in differentiated cells isolated from Gpr41/43 dKO mice. Overall, these data indicate that acetate regulates bone architecture via SCFA-Gpr41/43 signaling by modulating the osteogenic versus adipogenic differentiation of mesenchymal stem cells.